Aqueous Biphasic Systems Containing Customizable Poly(Ionic Liquid)s for Highly Efficient Extractions. Issue 7 (3rd March 2020) - Ke, Yuqi; Zhang, Jingzhu; Xie, Yuanbang; Yang, Qiwei; Ren, Qilong; Xing, Huabin
Abstract: Ionic liquid (IL)‐based aqueous biphasic systems (ABSs) provide a sustainable and efficient alternative to conventional liquid–liquid extraction techniques and can be used for the extraction, recovery, and purification of diverse solutes. However, the construction of a high‐performance ABS that has both excellent phase separation ability and extraction performance remains challenging. This study concerns the preparation of a family of novel ABSs based on poly(ionic liquid)s (PILs) with customized structure and controllable molecular weight for the extraction of bioactive compounds. Several tailor‐made PILs consisting of a hydrophobic backbone, hydrophilic imidazolium pendant groups and strong hydrogen bonding basic counteranions are prepared by reversible addition fragmentation chain‐transfer polymerization. The PILs have a perfect balance of hydrophobicity/hydrophilicity and functionality, affording outstanding phase separation, which was better than with either the IL monomer poly(1‐butyl‐3‐vinylimidazolium bromide ([BVIm]Br) or the normal free‐radical polymer P[BVIm]Br*. More importantly, PIL‐based ABSs exhibited unprecedented high partition coefficients for six bioactive compounds including tryptophan, phenylalanine, and caffeine, as well as high extraction yields. The performance of the PIL‐based ABSs could also be tuned by changing the molecular weight and anionic character of the PILs. This work shows that tailor‐made PIL‐based ABSs are a promising platform for bioactive compound extraction and provides significant clues for the design of new ABSs for various applications. Abstract : Flex those ABSs : Aqueous biphasic systems (ABSs) based on poly(ionic liquid)s (PILs) were designed and used for the extraction of bioactive compounds. Extraordinary partition coefficients were achieved by customizing the structure of the PILs. The performance of the PIL‐based ABSs was tuned by changing the molecular weight and anionic character of the PIL.